Dens evaginatus on a wisdom tooth: a diagnostic dilemma. case report - Ngeow, Wei Cheong; Chai, W.L. (AUSTRALIAN DENTAL ASSN INC, 116 PACIFIC HIGHWAY, SYDNEY, NSW 2060, AUSTRALIA, 1998)
Pericoronitis is the most common odontogenic problem associated with the wisdom tooth in young men and women. Patients may present with problems associated with infection, swelling and pain. However, other associated pathology such as caries, periodontal disease and referred pain from the temporomandibular joint must be investigated when treating pain from the wisdom tooth. The authors wish to present a case in which the pain from a wisdom tooth was due to a fractured dens evaginatus. The importance of this dental anomaly should not be overlooked.